Pengaruh Struktur Organisasi Terhadap Kinerja di Area Peternakan Kawasan Living Lab Glugur Rimbun - Hidayati Purnama Lubis; Suryani Sajar; Minarti Sri Wachyuni; Annisa Eka Maghfiroh; Muhammad Caisar Tarigan; Muhammad Azril (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The goal and main issues discussed in this research are how the Organizational Structure influences Performance in the Livestock Farming Area of Al Amin Science and Industrial Park (Living Lab) Glugur Rimbun. This study uses a qualitative associative method, conducting a review of theories and literature, as well as surveys and observations, and collecting opinions from academic community members, especially professors specializing in Human Resources. The research results state that organizational structure is a framework or arrangement that regulates relationships, responsibilities, and authorities within an organization. In management, organizational structure can be considered the foundation or operational framework of an organization. It is a fundamental element that forms the basis for organizing and directing organizational activities. There are several types of organizational structures that can be applied, and the selection of such a structure depends on the organization's goals, size, complexity, and needs. The choice of organizational structure should consider the organization's strategic goals, size, external environment, and the culture to be established. Moreover, organizations can change their structure over time to adapt to changing needs and business dynamics. The importance of organizational structure is reflected in its operational efficiency. By systematically mapping tasks and responsibilities, the structure creates a regular workflow, avoids unnecessary overlap, and establishes a foundation for optimal efficiency.